PERSEPSI GURU TERHADAP PENDEKATAN DEEP LEARNING PADA KURIKULUM MERDEKA BELAJAR DI SD NEGERI JARAKAN KEC SEWON BANTUL - Yulia Saputri; Hermawan Wahyu Setiadi (STKIP Subang, 2026)
This study aims to analyze teachers’ perceptions of the deep learning approach in the implementation of the Merdeka Curriculum at SD Negeri Jarakan, Sewon District, Bantul Regency. This research employed a qualitative approach with a naturalistic type and intrinsic case study design. The research subjects consisted of three fifth-grade teachers who were selected purposively based on several criteria, namely actively implementing the Merdeka Curriculum and having teaching experience of more than three years. Data collection techniques were conducted through in-depth interviews, participatory observation, and documentation studies. Data analysis used the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The results showed that teachers had a positive perception of the deep learning approach in the implementation of the Merdeka Curriculum. Teachers understood deep learning as a learning process emphasizing active student involvement, meaningful learning, reflection, and contextual learning related to students’ daily lives. The implementation of deep learning was carried out through educational games, group discussions, interactive learning media, reflective questions, and contextual learning activities. In addition, the Merdeka Curriculum provided flexibility for teachers to develop creative and student-centered learning. However, teachers still faced several obstacles, including limited learning time, administrative workload, diverse student characteristics, and limited practical understanding of deep learning implementation. Therefore, support through training, mentoring, and adequate educational facilities is needed to optimize the implementation of deep learning in elementary schools.